The Mineralogy of Naujakasite. - Petersen, Ole V. (Meddelelser om Grønland, 1967)
Naujakasite occurs as platy rhomb-shaped, silvery white crystals in the lujavrite at two localities Tuperssuatsiait and Kvanefj eld, in the Ilimaussaq alkaline intrusion, South Greenland. Occasionally naujakasite constitutes about three quarters of the rock. The crystals are monoclinic with three distinct cleavages; 001 mica-like, 010 and 401 distinct but somewhat irregular. (001): (401 ) = 93°. The density is 2.262 g/cm3, the hardness 2½-3. Naujakasite is biaxial negative, with 2Vα between 52° and 71°, nα = 1.537, nβ = 1.551 - 1.549, nγ = 1.556, 2Vα calculated= 62°- 75°. Ʇ(001): y = + 45 °. X-ray diffraction yields: a0 = 15.039 Å, b0 = 7.991 Å, c0 = 10.487 Å and β = 113.67° . Vol. 1154 Å3. Space groups C 2/m, Cm or C2. The formula (Na, K)6 (FeII, Mn, Ca) (Al, FeIII)4 Si8O26 • H2O, Z = 2 is proposed for the naujakasite although there are some differences between observed and theoretical values.